Strategic Purchasing for Better Health in Armenia - Chukwuma, Adanna (World Bank, Washington, DC, 2020)
This report is an activity under the technical support towards universal health coverage in Armenia, which includes advisory services and analytics aimed at supporting the government’s efforts to expand access to high-quality health care. The report, Strategic Purchasing for Better Health in Armenia, draws on an adaptation of the strategic purchasing progress framework to examine the country’s experience in purchasing healthcare, identify contextual factors that limit the potential of purchasing to reform healthcare, and integrate these findings with relevant global examples of strategic purchasing reforms. The authors conclude the report with tailored recommendations for strategic purchasing that can improve population health.